FAKTOR PENYEBAB KETERLAMBATAN PROYEK PEMBANGUNAN MASJID 99 KUBAH CENTER POINT OF INDONESIA MAKASS - Sidabutar, Genio Geofany; Latupeirissa, Josefine Ernestine; Meti, Meti (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
The construction of the 99 Dome Asmaul Husna Mosque Center Point of Indonesia Makassar has been delayed. Therefore the purpose of this study is to analyze the factors causing the delay in the construction of the mosque. The method of data collection was in the form of direct observation on the project and distributing questionnaires to those involved in the project, totaling 20 respondents. Test the validity and reliability of the 54 sub-factors of delay obtained from the results of literature review and observations in the field, categorized into 10 factors. Data analysis using RRI obtained 10 top ranking subfactors from seven factors. The conclusion based on the results of the research is that the sub-factors that cause delays in the implementation of the project sequentially are, the unexpected events of the COVID'19 pandemic, the RRI value = 0.892, the ability of the foreman or operator who is lacking in operating equipment, the RRI value = 0.800, the intensity of rainfall, the RRI value = 0.775, the workforce discipline, the RRI value = 0.767, the planned work order that is not well structured/integrated RRI value = 0.750, work space requirements RRI value = 0.750, payment difficulties by the owner RRI value = 0.742, access to the project location RRI value = 0.717, the work that has been completed must be corrected due to an error in processing the RRI value = 0.667, as well as the process of checking and evaluating the progress of work past the agreed schedule RRI value = 0.658